Differences In Student Learning Outcomes In The Educational Psychology Course Using The Project-Based Learning (PBL) Learning Model - kurniawan, Choirul; Kusmawati, Wiwik; Zaini, Moh.; Budijanto, Budijanto; Nuh, Fuad Azhar (Lembaga Penelitian dan Pendidikan Mandala, 2025)
The results of this study aim to determine the differences in student learning outcomes in the Educational Psychology course using the Project Based Learning (PBL) learning model. The research method is a quasi-experimental method. The sampling technique is simple random sampling. The sample is the Class I students of Class 2023 as the experimental class and the Class J students of Class 2023 as the control class. The data collection technique uses tests and non-tests. The instruments are multiple-choice objective tests and non-test instruments in the form of questionnaires. The data obtained were analyzed using prerequisite tests for normality tests and homogeneity tests. The results of the t-test that have been carried out with the SPSS program, obtained that the t-count value is greater than the t-table value, meaning that there is a significant difference in the learning outcomes of students in the experimental class and the control class, so it can be concluded that there is a difference in student learning outcomes in the Educational Psychology course using the PBL learning model.